Resetting FLOWERING LOCUS C Expression After Vernalization Is Just Activation in the Early Embryo by a Different Name - Finnegan, E. Jean; Robertson, Masumi; Helliwell, Chris A. (Frontiers in Plant Science, 2021)
The reproductive success of many plants depends on their capacity to respond appropriately to their environment. One environmental cue that triggers flowering is the extended cold of winter, which promotes the transition from vegetative to reproductive growth in a response known as vernalization. In annual plants of the Brassicaceae the floral repressor, FLOWERING LOCUS C (FLC), is down regulated by exposure to low temperatures. Repression is initiated during winter cold and then maintained as the temperature rises, allowing plants to complete their life cycle during spring and summer. The two stages of FLC repression, initiation and maintenance, are distinguished by different chromatin states at the FLC locus. Initiation involves the removal of active chromatin marks and the deposition of the repressive mark H3K27me3 over a few nucleosomes in the initiation zone, also known as the nucleation region. H3K27me3 then spreads to cover the entire locus, in a replication dependent manner, to maintain FLC repression. FLC is released from repression in the next generation, allowing progeny of a vernalized plant to respond to winter. Activation of FLC in this generation has been termed resetting to denote the restoration of the pre-vernalized state in the progeny of a vernalized plant. It has been assumed that that resetting must differ from the activation of FLC expression in progeny of plants that have not experienced winter cold. Considering that there is now strong evidence indicating that chromatin undergoes major modifications during both male and female gametogenesis it is time to challenge this assumption.